SUATU PENDEKATAN EKONOMETRI TERHADAP EKONOMI MAKRO INDONESIA (1978-1994) - Aris Soelistyo; Farid Wijaya Mansoer (Journal of Indonesian Economy and Business (JIEB), 1998)
An emperical study to Macroeconomic of Indonesia 1978.3-1994.4 with econometric approach, and be emphasized on its short run behaviour is directed to seek for the approval of treatment for sintesa Monetarist-Keynes in order to analysis Macro-economic of Indonesia by ekonometric method and though reduced form equation will try to express the impact ofgoverment expenditure, the riil exchange rate index, and the domestic credit changes to Income, price and Balance of Payment. The reduced form coefficient are called impact multiplier, since they measure the immediate response of the endogenous variables to changes in the predetermined variable. Debate and controversy between rival school economic thinking are conducted the theoritical level, the emperical level, and the policy level, especially, in order to express the Balance of payment. The Moneterist view balance of payment surplus and deficit as monetery flow due to stock disequilibrium in the money market or a balance of payment disequilibrium is a merely a reflection of a disequilibrium in the money market. Thus the monetary approach to the balance of payment asserts that the balance of payment involves essential monetary fenomena, in which that increase in income imply that the balance of payment improves, since the demand for money rises. On the other hand, the balance of payment expression in Keynes approach, however, associates increases in income with increased import and a detiorating balance of payment. Does this mean that the two approach provide conflicting views on the balance of payments. Actually, the different between them lies in the way the balance of payment is looked at, in which Keynes look at the balance of payment statistik from the top down (ie. the current account) while' the monetarist look for the bottom up (ie. the change in Reserve).